2020
DOI: 10.3390/ijms21165900
|View full text |Cite
|
Sign up to set email alerts
|

Hexobarbital Sleep Test for Predicting the Susceptibility or Resistance to Experimental Posttraumatic Stress Disorder

Abstract: Hexobarbital sleep test (HST) was performed in male Wistar rats (hexobarbital 60 mg/kg, i.p.) 30 days prior to stress exposure. Based on the duration of hexobarbital-induced sleep, rats were divided into two groups, animals with high intensity (fast metabolizers (FM), sleep duration <15 min) or low intensity of hexobarbital metabolism (slow metabolizers (SM), sleep duration ≥15 min). The SM and FM groups were then divided into two subgroups: unstressed and stressed groups. The stressed subgroups were expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…The conservativeness of high-anxiety rats might be connected to their metabolical state specifics. In our previous studies performed on Wistar rats [ 37 ], we also observed a lower variability in neuroendocrine changes in high-anxiety stressed rats compared with the low-anxiety group. At the same time, an interesting correlation was found between the level of anxiety and the level of microsomal oxidation, determined in vivo using the hexenal sleep test [ 37 ].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The conservativeness of high-anxiety rats might be connected to their metabolical state specifics. In our previous studies performed on Wistar rats [ 37 ], we also observed a lower variability in neuroendocrine changes in high-anxiety stressed rats compared with the low-anxiety group. At the same time, an interesting correlation was found between the level of anxiety and the level of microsomal oxidation, determined in vivo using the hexenal sleep test [ 37 ].…”
Section: Discussionsupporting
confidence: 60%
“…In our previous studies performed on Wistar rats [ 37 ], we also observed a lower variability in neuroendocrine changes in high-anxiety stressed rats compared with the low-anxiety group. At the same time, an interesting correlation was found between the level of anxiety and the level of microsomal oxidation, determined in vivo using the hexenal sleep test [ 37 ]. Additionally, animals with a long duration of hexenal sleep were considered slow metabolizers.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The comparison of corticosterone and testosterone levels in the blood serum demonstrated that the decrease in measured hormone levels of all rats exposed to stress ( Table 1 ). The reduction of corticosterone level is a generally accepted index of PTSD-like state development [ 6 , 10 , 12 , 13 ]. Nevertheless, the values of corticosterone levels in resistant rats were statistically higher than in sensitive ones ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous experiment showed that rats later becoming sensitive to stress prior to stress modeling had a higher corticosterone level. We managed to determine that cytochrome P4503A-mediated metabolism of glucocorticoids was prevailing in stress-resistant animals, whereas the metabolism of stress-sensitive animals depended from 11β-hydroxysteroid dehydrogenase type 2 [ 13 ].…”
Section: Resultsmentioning
confidence: 99%